The potential for coral reef establishment through free-living stabilization. Issue 1 (December 2017) - Hennige, S.; Burdett, H.; Perna, G.; Tudhope, A.; Kamenos, N.
Abstract Corals thrive in a variety of environments, from low wave and tidal energy lagoons, to high energy tidal reef flats, but remain dependent upon suitable substrate. Herein we reviewed the phenomenon of free-living corals (coralliths), examined whether they have the capacity to create their own stable habitat in otherwise uninhabitable, poor substrate environments through 'free-living stabilization', and explore their potential ecological role on coral reefs. This stabilization could be achieved by coral settlement and survival on mobile substrate, with subsequent growth into free-living coralliths until a critical mass is reached that prevents further movement. This allows for secondary reef colonization by other coral species. To preliminarily test this hypothesis we provide evidence that the potential to support secondary coral colonisation increases with corallith size. Due to the limited diversity of corallith species observed here and in the literature, and the lack of physiological differences exhibited by coralliths here to static controls, it seems likely that only a small selection of coral species have the ability to form coralliths, and the potential to create their own stable habitat.